Numerical Simulation and Experimental Validation of Sheet Laser Forming Processes Using General Scanning Paths - Garcia-Herrera, C; Cruchaga-Ssa., M; Navarrete-Rosales, A (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
This work presents numerical simulations and an experimental validation of sheet laser forming processes using general scanning paths with different laser beam operating parameters (i.e., power, diameter, and scanning speed) in two specific graphite coated stainless steel blanks (i.e., with thicknesses of 0.3 mm and 0.6 mm for the AISI 302 and 304 alloys, respectively). To this end, three specific laser forming tests involving single S-shaped, multiple circular, and single piecewise linear scanning paths are carried out. On the other hand, the numerical simulation of these tests is performed via a coupled thermomechanical finite element formulation, accounting for large viscoplastic strains, temperature-dependent material properties, and convection-radiation phenomena. The final bending angles provided by this model are found to be in good agreement with the experimental measurements for all of the cases studied. Therefore, this modeling framework can be established as a reliable approach to predict the material thermomechanical response during sheet laser forming using general scanning paths.